The design of fuzzy expert system implementation for analyzing transmissible disease of human - Fauzi; Huda M.; Teh K.S.M.; Haroon Z.; Ripin M.N.; Hehsan A.; Abas H.; Hehsan M.R.; Irawan J.; Abadi S.; Maseleno A. (Advanced Scientific Research, 2023)
allergic rhinitis; analytic method; Article; artificial intelligence; clinical decision making; communicable disease; coughing; data analysis; data processing; diagnostic accuracy; diagnostic error; fuzzy set method; human; influenza; pneumonia; sinusitis; working memory